Design And Evaluation Of Transdermal Films Of Lornoxicam - K. KAVITHA; MORE MANGESH RAJENDRA (International Journal of Pharma and Bio Sciences, 2011)
The current research work was an attempt to develop and evaluate matrix-type transdermal therapeutic system containing Lornoxicam with different ratios of hydrophilic and hydrophobic polymeric combinations by the solvent evaporation technique. The physicochemical compatibility of the drug and the polymers was studied by infrared spectroscopy. The results suggested no physicochemical incompatibility between the drug and the polymers. Three transdermal patch formulations (F1, F2 and F7) consists of Hydroxypropyl methyl cellulose E5 and Ethyl cellulose in the ratios of 5:0, 0:5 and 1:1, respectively were prepared. All formulations carried 4% w/v of Tween-80 as penetration enhancer for Lornoxicam and 10% w/v of Polyethylene glycol as plasticizer in dichloromethane and methanol (4:1) as solvent system. The prepared transdermal patches were evaluated for in vitro release, moisture absorption, moisture loss and mechanical properties. The diffusion studies were performed by using modified Franz diffusion cells. The formulation, F1 (Hydroxypropyl methyl cellulose E5 alone) showed maximum release of 95.76 ± 1.38 % in 8 h, where as F2 (Ethyl cellulose alone) showed maximum release of 58.64 ± 1.14 % in 24 h. The formulation, F3 with combination of polymers (1:1) showed maximum release of 76.76 ± 2.1 % in 24 h, emerging to be ideal formulations for Lornoxicam and the mechanism of release was diffusion mediated. The developed transdermal patches increase the efficacy of Lornoxicam for the therapy of arthritis and other painful muscular conditions.